Diversity of orchids in Taman Eden 100, Lumban Julu District, Toba Regency, North Sumatra, Indonesia - Arif Syahrizal; Luthfi Aziz Mahmud Siregar; Diana Sofia Hanafiah; Nurhasnah Manurung; Mohammad Nasrul Hakim Roslan (Universitas Islam Negeri Sumatera Utara, 2026)
Orchid diversity in tropical forest ecosystems is increasingly threatened by habitat degradation and land-use change, highlighting the importance of biodiversity assessments in conservation areas. This study aimed to determine orchid species composition, species diversity, and the physical environmental conditions supporting orchid habitats in Taman Eden 100, North Sumatra, Indonesia. The research was conducted from August to October 2023 using a descriptive–exploratory approach with purposive sampling. Five plots measuring 20 × 20 m were established in representative orchid habitats. Data were analyzed descriptively using relative density, relative frequency, relative dominance, the Important Value Index (INP), and the Shannon–Wiener diversity index. A total of 77 orchid species were recorded, comprising 51 epiphytic species (66%) and 26 terrestrial species (34%). Thelasis micrantha was the most abundant species, with 178 species and the highest INP (12.99%), whereas Bulbophyllum odoratum was the least abundant species, represented by a single species with an INP of 0.22%. The orchid habitats were characterized by air temperatures of 21-27°C, relative humidity of 94-97%, soil pH of 6.5-6.8, and elevations ranging from 1,200 to 1,350 m asl, providing favorable conditions for orchid growth. These findings demonstrate that Taman Eden 100 supports high orchid diversity and serves as an important conservation area for preserving native orchid resources in North Sumatra